Some notes about Environmental Psychology - Valera Pertegás, Sergi (2021)
Environmental Psychology as a discipline focuses on an applied character by paying attention to the processes that guide the relationship between people and their environments. As a result, it provides criteria for intervening on the physical context from a psychological and social perspective. To do this, it is necessary to expand the concept of environment beyond its physical characteristics to understand it as a socio-physical environment, a cross between environmental variables and meanings on which the human environmental experience is based. In this paper, we introduce Environmental Psychology as a scientific discipline. Moreover, the articulation between the physical and psychosocial aspects of the environment is discussed. Finally, some cases of intervention in urban public art are analyzed, whose disparate impacts illustrate how the activation of various processes of environmental meaning determines our relationship with the environment.